Pd-Phosphinesulfonate bravely battles the ``vinyl halide insertion copolymerization'' barricade - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2014)
This overview provides insights into the current state-of-the-art solutions to insertion copolymerization of functional olefinic monomers. The challenges in insertion copolymerization of functional olefinic monomers, with a special emphasis on vinyl halides, are highlighted. The crucial design of the Pd-phosphinesulfonate [Pd(PO)] enables up to 3.6 mol % incorporation of vinyl fluoride (VF) in an ethylene-VF copolymerization reaction. In a significant development, insertion copolymerization of industrially relevant functional olefin, that is, vinyl chloride (VC), was unambiguously ascertained, and a detectable amount of VC (0.4 mol %) was incorporated (at the chain end). In a detailed investigation, the in situ existence of (PO)PdH species during the polymerization was revealed, and it was demonstrated that these are indeed responsible for VC incorporation. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1-6
Keywords: functional olefin; insertion copolymerization; palladium catalyst; phosphinesulfonate; vinyl chloride

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Pd-iminocarboxylate complexes and their behavior in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Gonnade, Rajesh G.; Pandole, Satish P.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2020)
Designing co-catalyst-free late transition metal complexes for ethylene polymerization is a challenging task at the interface of organometallic and polymer chemistry. Herein, a set of new, co-catalyst-free, single-component catalytic systems for ethylene polymerization have been unraveled. Treatment of anthranilic acid with various aldehydes produced four iminocarboxylate ligands (L1-L4) in very good to excellent yield (75-92 %). The existence of 2-((2-methoxybenzylidene)amino) benzoic acid (L1) has been unambiguously demonstrated using NMR spectroscopy, MS and single-crystal X-ray diffraction. A neutral Pd-iminocarboxylate complex [N OPdMe(L1)] (N O=kappa(2)-N,O-ArCHNC6H4CO2 with Ar=2-MeOC6H4) C1 was prepared by treating stoichiometric amount of L1.Na with palladium precursor. The identity of C1 was confirmed by 1-2D NMR spectroscopy and single-crystal X-ray diffraction studies. Along the same lines, palladium complexes C2-C4 were prepared from ligands L2-L4 respectively. In-situ high-pressure NMR investigations revealed that these Pd complexes are amenable to ethylene insertion and undergo facile beta-H elimination to produce propylene. These palladium complexes were then evaluated in ethylene polymerization reaction and various reaction parameters were screened. When C1-C4 were exposed to ethylene pressures of 10-50 bar, formation of low-molecular-weight polyethylene was observed.
Keywords: imine; Imine-carboxylate; Insertion polymerization; Pd complexes; Polyethylene

Phosphorus ligands in hydroformylation and hydrogenation: a personal account - Tewari, Tanuja; Kumar, Rohit; Chandanshive, Amol C.; Chikkali, Samir H. (Chemical Record, 2021)
Metal-catalyzed hydroformylation and hydrogenation heavily rely on ligands, among which phosphorous ligands play a pivotal role. This personal account presents a selection of three distinct classes of phosphorous ligands, namely, monodentate meta-substituted phosphinites, bis-phosphites, and P-chiral supramolecular phosphines, developed in our group. The synthesis of these ligands, isolation, characterization, and their performance in transition metal-catalyzed hydroformylation, isomerizing hydroformylation, and asymmetric hydrogenation of olefins is summarized. The state of the art development in iron-catalyzed hydroformylation of alkenes and our contributions to the field is discussed. Use of phosphines enabled iron-catalyzed hydroformylation of alkenes under mild conditions. Thus, this account demonstrates the central role of phosphorus ligands in industrially relevant transformations such as hydrogenation and hydroformylation. The seemingly matured field of ligand discovery still holds significant potential and will steer the field of homogeneous catalysis.
Keywords: Homogeneous catalysis; Hydroformylation; Hydrogenation; Olefins; Phosphorus ligands

Palladium-catalyzed polar solvent empowered synthesis of hyper-branched ethylene oligomers and their applications - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Pol, Harshawardhan V.; Prabhu, M. Basava; Rokade, Dhammaraj; Nandimath, Sheetal; Chikkali, Samir H. (Polymer Chemistry, 2023)
In this contribution, we report the synthesis of two naphthoxy imine ligands, 2-(((2,6-dibenzhydryl-4-methoxyphenyl)imino)methyl)naphthalen-1-ol (L1) and 2-(((2,6-diisopropylphenyl)imino)methyl)naphthalen-1-ol (L2), with different steric and electronic features. L1 and L2 were treated with [(TMEDA)PdMe2] to obtain the corresponding neutral palladium(ii) complexes Cat.1 and Cat.2 in excellent yields. The identity of Cat.1 and Cat.2 was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. When exposed to 5 bar ethylene pressure, Cat.1 produced hyperbranched ethylene oligomers. The microstructure analysis of ethylene oligomers confirmed the existence of methyl, ethyl, propyl, and sec-butyl branches, with a molecular weight (M-n) of 500-1400 g mol(-1), a PDI of 1.46-2.10, and 67-106 branches per 1000 carbon atoms. The use of a polar solvent, tetrahydrofuran, led to a remarkable 3-fold increase in oligomerization activity without compromising the branching and molecular weight. The resultant hyperbranched ethylene oligomers were selectively monofunctionalized using industrially practiced hydroformylation, ozonolysis, and epoxidation, almost quantitatively. The hydroxy functionalized ethylene oligomer (F4) (5 wt%) was melt-compounded with LLDPE and Nylon-6 to produce a tough yet flexible blend with a higher strain-to-failure as compared to an uncompatibilized blend.

Polyethylene-grafted sheet-like silsesquioxane nanocomposites with unprecedented adhesion to polar substrates - Sharma, Vivek; Paulbudhe, Uday; Bachhar, Nirmalya; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2023)
Polyethylene is a highly apolar polymer with very pooradhesionto most substrates, necessitating the use of tie layers. Therefore,the synthesis of functional polyethylene is a long-standing challengein catalytic ethylene polymerization. Here, we report the preparationof a nanocomposite comprising polyethylene covalently grafted ontosheet-like silsesquioxanes, with unprecedented adhesion to metal andglass. A norbornene-grafted, layered Mg-silsesquioxane is treatedwith Grubbs second-generation catalyst (G-II), and the identity ofcovalently tethered G-II is unambiguously ascertained. Covalentlytethered G-II catalyzes the ring opening metathesis polymerizationof cyclooctene to poly(cyclooctene). The resulting poly(cyclooctene)is catalytically hydrogenated to yield polyethylene. This polyethylenenanocomposite exhibited a bonding strength of the order of 100 MPaon stainless steel and aluminum, 10-fold higher than reported forengineered polyethylene copolymers. The nanocomposite exhibits anincrease in the polar component of surface energy, yet remains compatibleand cocrystallizes with a polyethylene matrix.
Keywords: adhesion; clay; Nanocomposite; Polyethylene; silsesquioxane

P-chiral organophosphorus compounds: synthesis, mechanism, and applications - Chandanshive, Amol C.; Chikkali, Samir H. (Chemistry-an Asian Journal, 2026)
The enantioselective synthesis of P-stereogenic compounds has emerged as a central focus in modern asymmetric catalysis, driven by their pivotal roles as ligands (Ls), organocatalysts, and bioactive molecules. Over the past decade, significant advances have been made in developing catalytic strategies that enable precise control over phosphorus stereochemistry, expanding both the structural diversity and synthetic utility of these scaffolds. This review highlights recent progress in two key areas: direct P-C bond formation and desymmetrization. P-C bond-forming approaches include cross-coupling reactions of secondary phosphines or their oxides with aryl, alkyl, or benzyl halides, as well as hydrophosphination of alkenes and alkynes. Desymmetrization strategies encompass nucleophilic substitution at P(V) centers, cyclization, C-H activation (CHA), phenolic -OH activation, and P-O alkylation/arylation. Mechanistic insights into these transformations have been discussed, along with the derivatization of P-chiral products and their applications in catalysis, L design, and bioactive molecule synthesis. This comprehensive overview shall serve as a valuable resource for researchers working in asymmetric organophosphorus chemistry.
Keywords: desymmetrization; Hydrophosphination; P-C cross coupling; P-chiral phosphines; phosphination